Distinct Patterns of B-Cell Activation and Priming by Natural Influenza Virus Infection Versus Inactivated Influenza Vaccination - He, Xiao-Song (J Infect Dis, 2015)
Background. The human B-cell response to natural influenza virus infection has not been extensively investigated at the polyclonal level. Methods. The overall B-cell response of patients acutely infected with the 2009 pandemic influenza A(H1N1)pdm09 virus (A[H1N1]pdm09) was analyzed by determining the reactivity of plasmablast-derived polyclonal antibodies (PPAbs) to influenza proteins. Recipients of inactivated influenza vaccine containing the same A(H1N1)pdm09 strain were studied for comparison. Results. During acute infection, robust plasmablast responses to the infecting virus were detected, characterized by a greater PPAb reactivity to the conserved influenza virus nuclear protein and to heterovariant and heterosubtypic hemagglutinins, in comparison to responses to the inactivated A(H1N1)pdm09 vaccine. In A(H1N1)pdm09 vaccinees, the presence of baseline serum neutralizing antibodies against A(H1N1)pdm09, suggesting previous exposure to natural A(H1N1)pdm09 infection, did not affect the plasmablast response to vaccination, whereas repeated immunization with inactivated A(H1N1)pdm09 vaccine resulted in significantly reduced vaccine-specific and cross-reactive PPAb responses. Conclusions. Natural A(H1N1)pdm09 infection and inactivated A(H1N1)pdm09 vaccination result in very distinct patterns of B-cell activation and priming. These differences are likely to be associated with differences in protective immunity, especially cross-protection against heterovariant and heterosubtypic influenza virus strains.